Quantifying the Use of Stones in the Stone Age Fireplaces of Estonia - Sikk, Kaarel (Archaeologia Lituana, 2017)
Fireplaces and burnt stones related to them are common features found at Stone Age settlement sites. Although informatikon about them is present in archaeological reports and also available in publications, there has been no general research done regarding combustion features specifically. The purpose of this study was to fill the gap of relevant research and to test the hypothesis that the structural features of fireplaces reveal information on the subsistence model of settlements.The study is based on a database of Estonian Stone Age fireplaces, which was compiled by using the available data on all excavated objects. The database includes 167 fireplaces and contains quantifiable data about stones in fireplaces.The analysis of data revealed that the use of stones in fireplaces changed significantly in time. While most of the Mesolithic fireplaces contain them, they become scarce in the Neolithic. It can be concluded that the use of stones in fireplaces is related to the economy of settlements and changes within time reflect the changes in general subsistence strategies.
Keywords: fireplaces; hearths; quantitative analysis; reuse of data; Mesolithic; Neolithic